Desenvolvimento e avaliação da qualidade de óleo alternativo para fritura dos alimentos usando diferentes recipientes - Freitas, Lindeberg Rocha (2007)
In this work deals with the quality of vegetable oils. Thus, refined oils from soybean (Glycine max L), both conventional and transgenic, and the crude and refined oils of nhandiroba (Fevillea trilobata L) were investigated. All the oil samples were studied before, during and after the frying process. The oxidative process of these oils was also quantified. With this purpose, the vegetable oils were submitted to the temperature (180 ± 50 oC) in recipients of glass, aluminum, iron and stainless steel. The oil samples were collected in aliquots of 10 ml each, at time intervals of 0, 8, 24, 48 and 72 hours. The analyses of acid value, iodine value, peroxide value, panisidine content and color were carried out. The quantification of the iron and aluminum ions was undertaken by atomic absorption. The quantification of a- tocopherol in crude nhandiroba oil was determined by HPLC. The thermal stability of the oils was assessed using the thermogravimetric curves and the chromatograms of the studied oil samples. The toxicological properties were evaluated; as well organoleptic tests were performed. In vivo laboratorial tests studied the icthyotoxicity in Poecilia reticulata L. alevins and the cytotoxicity in Artemia saline L. larvae. In the sensorial analysis hedonic tests were applied and the following attributes were appraised: aspect, flavor, scent and texture of chicken and fish croquettes. The croquettes were fried in recipients of glass, utilizing refined conventional soybean and nhandiroba oils. The results showed that all the oils investigated during the 72 hours of frying, in the four types of recipients, displayed increasing figures of peroxide value, p-anisidine content and color. The acid value varied, whereas the iodine value decreased. The vegetable oil made from conventional soybean presented important oxidative alterations, when submitted to a heating time of 72 consecutive hours in the four different types of frying recipients. In the recipients of iron and stainless steel, such differences were larger than in the aluminum and glass recipients. The results of the transgenic soybean oil, crude and refined nhandiroba oils showed mild oxidative modifications in all the four types of recipients tested. In the frying process, the physico-chemical properties of the vegetable oils influenced the sensorial profile of the victuals. It was observed for the sensorial property aspect that there was no meaningful difference between the two oil types, in other words, the aspects of the fried croquettes in the two oils were considered to be the same. In the evaluation of the attributes scent, texture and flavor, it was noticed, for the chicken croquettes, a difference between the two oil types. The conventional soybean oil was better accepted, obtaining the best notes. In the frying of the fish croquette, the nhandiroba oil displayed the best sensorial characteristics. Therefore, in the frying process the cooking recipients of glass, aluminum, iron and stainless steal exert a deleterious influence on soybean oils, as well as on nhandiroba oils. The iron recipient is the one that provokes the largest oxidative effect and the glass recipient the one with the smallest oxidation damage. These alterations, which took place in the investigated oils, influence their quality.